When reorganizing coercion backfires: explaining the mechanisms of revolt in Sudan and Algeria. Issue 7 (3rd October 2022) - Langlois, Jérémie
ABSTRACT: When autocrats seek to coup-proof coercive institutions after revolts, how does it affect future revolutionary mobilization? Scholars of contentious politics describe the mechanisms by which citizens can oust autocrats from the streets, while the literature on civil–military relations asks how rulers mitigate elite threats by restructuring their barracks. This article introduces the concept of reorganizing coercion to investigate how the effects of restructuring armed state actors can resonate in society and strengthen revolutionary mobilization. Using the cases of Sudan and Algeria, I trace the way both regimes reorganized coercion following the Arab Spring and argue that these processes interacted with economic shocks to affect one collective action issue during the 2018–2019 uprisings: mobilization across centre-periphery cleavages. Three iterative mechanisms define this relationship: the reorganization of coercive institutions, resource policies influenced by the reorganization of coercive institutions, and the spatiality of repression shaped by both aforementioned factors. I develop this plausibility probe through an analysis of protest data and process tracing that leverages original interviews as well as secondary sources in Arabic, French, and English. By suggesting that reorganizing coercion might explain similarities between these cases, this study shows how the concept can bridge debates between contentious politics and civil–military relations.